Health Promotion Strategies for Managing Exercise Intensity and Duration Among Athletes: A Scoping Review - Donna Novina Kahanjak; Ilhamjaya Patellongi; Mushawwir Taiyeb; Nukhrawi Nawir; Ira Jayanti; Evan Kristanto Gampa (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Regular physical exercise offers substantial benefits to cardiovascular health by improving aerobic capacity, cardiac efficiency, and reducing the risk of cardiovascular disease. However, excessive or unregulated training may lead to maladaptive cardiac remodeling and increase the risk of arrhythmias or sudden cardiac death. Understanding the physiological boundaries of exercise-induced cardiac adaptation is therefore crucial for promoting safe and effective athletic performance. Methods: This scoping review followed a systematic protocol based on the PEOS framework (Population, Exposure, Outcome, Study Design). Literature searches were conducted in PubMed, ScienceDirect, EBSCO, and Google Scholar for studies published between 2000 and 2024 using relevant keywords on cardiac responses to exercise. Inclusion criteria covered original research and reviews focusing on cardiac adaptation, remodeling, and training intensity among athletes. From an initial 512 records, 20 eligible studies were critically appraised and synthesized using a narrative approach. Results: Endurance training predominantly induced eccentric hypertrophy and increased left and right ventricular volumes without systolic dysfunction, while resistance training produced concentric hypertrophy due to higher pressure load. These structural adaptations were physiological, reversible, and not associated with fibrosis. Conversely, extreme endurance activities were linked to transient cardiac fatigue and elevated cardiac biomarkers. Detraining studies confirmed regression of cardiac mass, highlighting the reversible nature of physiological remodeling. Conclusion: Cardiac responses to exercise depend on training intensity, duration, and type. Physiological remodeling enhances cardiovascular function, whereas excessive training or genetic predispositions may lead to pathological consequences. Balancing load and recovery, alongside periodic medical evaluation, is essential to optimize performance and prevent cardiovascular complications.